The Notary's Role in the Process of Making a Deed of Change in Management of CV - Strenfort, Logan; Victoria, Ong Argo (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
This reasearch aims to determine and analyze the role and legal position of the Notary in making a deed of change in management of a limited partnership company (CV) due to death, the legal position of the deed clauses made by a Notary in making a deed of change in management of a limited partnership company (CV) because of death. The approach method used in this research is a sociological juridical approach, meaning research carried out on the real conditions of society or the community environment with the aim and purpose of finding facts which then lead to identification and ultimately lead to problem solving. The analytical knife in this writing uses the theory of authority and the theory of legal certainty. The results of this research show that the procedure for changing the CV management company by a successor is that there must be provisions confirming the ability to continue the CV must be clearly stated in the CV's articles of association agreement, after which all deeds are registered and announced in the Supplement to the State Gazette. Legal protection must look at stages, namely legal protection is born from legal provisions and legal regulations provided by society. Basically, legal regulations are a community agreement to regulate behavioral relationships between members of society and between individuals and the government which is considered to represent the interests of society. In general, protection means protecting something from dangerous things, something that could be interests or objects or items. Apart from that, protection also means protection given by someone to someone who is weaker.